Implementation of E-Govqual and IPA Models in Evaluating the Quality of Online Licensing System Services - Pangestu, Danu Faisal; Wahyu, Sawali (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
The online licensing information system website, hereinafter referred to as SIMPONIE, still faces a number of challenges as a transition from manual to digital system and has never been properly checked on the SIMPONIE website. This study aims to assess the good and bad level of SIMPONIE services using six e-govqual dimensions and provide advice based on the results of the Importance Performance Analysis (IPA) analysis. Research development on this method covers the wider scope of service quality. This study used a quantitative descriptive approach to collect data from 50 sample questionnaires and to carry out validity and reliability checks along with hypothesis testing and IPA quadrant analysis. According to the research results, 90.5% of the choices regarding service quality are influenced by factors of community support, function, and involvement as well as user convenience, reliability, and trust. With a gap value (GAP) of -0.75, there is a high priority scale for improvement in quadrant A, namely the license issuance function will be faster if it can be downloaded independently (RLB 2), the system often experiences errors or errors (FI 4) and live chat feature that needs improvement and human resource improvement. The implication of this research is that it can provide recommendations for improvements to improve the service quality of the online licensing system.